The escarpão plateau (South of Portugal)—a study case of nested geosites from the aspiring Algarvensis geopark - Veiga-Pires, Cristina (2024)
Located along the southern limit of the Algarvensis aspiring UNESCO Global Geopark (aUGGp), the Escarpão Plateau is a singular geomorphological structure sculpted by fluvial, karst, and tectonic processes. The plateau is deeply scarved by the Quarteira Rivulet, forming a valley that crosses the most complete Upper Jurassic sedimentary sequence of the Eastern Algarve (Southern Portugal). This sequence includes five geological formations representing different depths of carbonate ramp deposition from the Tethys Sea: Peral Formation, Jordana Formation, Cerro da Cabeça Formation, Escarpão Formation, and the upper Limestone Formation with Anchispirocyclina lusitanica (foraminifera), respectively from the oldest formation to the most recent at the top. Throughout the Quaternary Period, the karst processes shaped a landscape of sparse and poor soils, based on which successive generations adapted their subsistence agriculture and way of life. The geomorphology of the plateau and the rivulet valley, the sequence of the carbonated formations, and the diversity of sedimentary and paleontological records can be considered possible sites of diverse geological interest and with different scales that are embedded in each other, forming thus nested sites. To promote and preserve these sites, the Algarvensis aUGGp shaped an 8-km-long interpretative walking path, passing through 11 points of interest, including biosites and geosites. Their interpretative boards highlight not only the different spatial and temporal geological diversity but also its relationship with surrounding cultural and historical heritage. Finally, this work allowed the creation of new products for outreach and public awareness towards an effective geoconservation.